Adanya Online Shop Terhadap Perilaku Konsumtif Di Kalangan Mahasiswa Sosiologi Untirta Angkatan 2020 - Siti Azahra Sihab; Dema Tesniyadi; Rizki Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
An online store is a way to carry out public sale transactions via the Internet. Online stores allow people to get the products they want without leaving their homes. Internet use by students cannot be separated from consumption patterns by online retailers. Advances in telecommunication technology have made it easier for students to transact and sell goods, goods and services in online shops. Not only are they customers, but they are also online store owners. The purpose of this study was to investigate the impact of using an online shop on the buying habits of Untirta students Batch 2020. This research uses a descriptive approach by describing, demonstrating, and describing a research phenomenon, namely campus life using online shops. This technique conveys object data in a natural, objective, and fact-based manner. This study takes a qualitative approach because it is based on scientific evidence, uses natural methodologies, and is conducted by researchers interested in the natural world. From this research, it can be seen that female students use online shops for a reason. It also turns out that female students use online shops mainly to enhance and improve their lifestyle with popular themes, especially in artist styles. College students with more money can also buy their favorite clothes online. And with the convenience of shopping, it creates consumptive behavior among Untirta Sociology students Batch 2020.